Analysis of policy implementation of local public service agency in hospital - Roza, Shelvy Haria; Angelia, Inge (International Journal Of Community Medicine And Public Health, 2018)
Background: The level of public satisfaction with public hospital services is still quite low, with almost more than 50% complaining about the services it receives. The demand for hospital service quality, the government imposed the policy of local public service agency (LPSA) in the hospital. This study aimed to analyze the implementation of LPSA policy. Methods: This research was a descriptive research with qualitative approach. This research was conducted in Dr Rasidin Hospital in Padang, during July to October 2017. Key informants were chosen by purposive sampling as many as five people who understand about LPSA policy. Data were collected through indept interview, document review, and observation. Qualitative data were analyzed by thematic analysis. Results: The result of the research showed that the implementation of LPSA policy from policy standard has been run well, has a sufficient and adequate resources. Disposition of executives were positive in support of this policy to service activities. Communication has not spread evenly across all employees, only revolving around employees who directly handle the local public service agency. The bureaucratic structure was clear. Conclusions: Implementation of public service agency policies has worked well in terms of the standard policy, disposition, resources, communications, bureaucratic structure.